To Keep Her Breathing: A Novella Exploring How Long-Term Depression Affects Women’s Health - Rachel Immanuel; Liliek Soelistyo (Institute of Research and Community Outreach - Petra Christian University, 2025)
This creative thesis incorporates a cyberpunk dystopian narrative to study the effects of long-term depression on women's physical health by showing the connection between psychological stress and physical decline. It highlights the often-overlooked reality that untreated stress can manifest as chronic pain, sleep disturbance, and cardiovascular issues. These ideas will be developed into a cyberpunk dystopian novella supported by Slavich and Irwin’s Inflammation Theory of Depression (2014) and the concept of Socio-economic Marginalization by Hall and Carlson (2016). The narrative mainly focuses on Li, a woman who suffered from depression throughout her life because of childhood trauma and continuous emotional abuse. As her mental health deteriorates, she experiences migraines, insomnia, and hypertension. Throughout the narrative, Li is offered the opportunity to get better using psychological treatment and stress-reducing practices like meditation. Her journey provides a reminder that recovery is possible by facing trauma, taking back control, and gradually coming to terms with her condition to improve her health and self-worth.